Eco-Friendly Method Development and Validation for the Estimation of Fenofibrate and Atorvastatin in Marketed Formulation - Irshad Ali; BK Dubey; Deepak Kumar Basedia; Prabhat Kumar Jain; Sunil Shah; Vivek Singh Thakur (Current Research in Pharmaceutical Sciences, 2024)
This study focuses on the development and validation of an eco-friendly analytical method for the simultaneous estimation of Fenofibrate (FNF) and Atorvastatin (ATV) in a marketed formulation. The stability of both drugs was evaluated using a mixed hydrotropic solution of 2M Ammonium Acetate and 2M Sodium Citrate (1:1). This work focuses on the development and validation of an eco-friendly method for the simultaneous estimation of Fenofibrate and Atorvastatin in a marketed formulation. The stability of both drugs in a mixed hydrotropic solution was confirmed, and the method exhibited good linearity, recovery, and precision. The validated method was successfully applied to analyze a tablet formulation, demonstrating its applicability in routine quality control. The use of environmentally friendly practices in analytical methods contributes to sustainable pharmaceutical analysis.